2008
DOI: 10.1152/ajpheart.00610.2008
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous zinc protects cardiac cells from reperfusion injury by targeting mitochondrial permeability transition pore through inactivation of glycogen synthase kinase-3β

Abstract: The purpose of this study was to determine whether exogenous zinc prevents cardiac reperfusion injury by targeting the mitochondrial permeability transition pore (mPTP) via glycogen synthase kinase-3beta (GSK-3beta). The treatment of cardiac H9c2 cells with ZnCl2 (10 microM) in the presence of zinc ionophore pyrithione for 20 min significantly enhanced GSK-3beta phosphorylation at Ser9, indicating that exogenous zinc can inactivate GSK-3beta in H9c2 cells. The effect of zinc on GSK-3beta activity was blocked b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 45 publications
2
66
0
Order By: Relevance
“…It has been reported that the level of zinc decreased during reperfusion by excessive zinc loss in ischemic/reperfusion injury (Chanoit et al 2008;Xu et al 2014). Besides this finding, the lipid activates the PKC which triggers the zinc release, so, we envisage the hyperlipidemia model for study.…”
Section: Introductionmentioning
confidence: 89%
“…It has been reported that the level of zinc decreased during reperfusion by excessive zinc loss in ischemic/reperfusion injury (Chanoit et al 2008;Xu et al 2014). Besides this finding, the lipid activates the PKC which triggers the zinc release, so, we envisage the hyperlipidemia model for study.…”
Section: Introductionmentioning
confidence: 89%
“…Therefore, it is reasonable to conclude that morphine modulates the mPTP opening by inactivating GSK-3␤ through Zn 2ϩ . As to the mechanism by which mobilized Zn 2ϩ inactivates GSK-3␤, we assume that Zn 2ϩ may inhibit GSK-3␤ through the Akt/ phosphatidylinositol 3-kinase signaling pathway, as we documented previously (4).…”
Section: Discussionmentioning
confidence: 93%
“…First, exogenous NO (11) mobilizes intracellular Zn 2ϩ through the cGMP/PKG pathway and morphine can produce NO in cardiomyocytes (20). Second, Zn 2ϩ inhibits the mPTP opening by inactivating GSK-3␤ in cardiac cells (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, [Zn 2ϩ ] i may increase concomitantly with [Ca 2ϩ ] i under pathological conditions such as ischemia/hypoxia (5,6,10,11), in which intracellular Ca 2ϩ overload is suspected to contribute to cell death in these conditions (12). However, whether such increases in [Zn 2ϩ ] i contribute to the deleterious effect or play a compensatory cell-protective effect is not clear (5,11,(13)(14)(15)(16).…”
mentioning
confidence: 99%